Hypertension in cancer patients treated with anti-angiogenic based regimens. Issue 1 (December 2015) - Wasserstrum, Yishay; Kornowski, Ran; Raanani, Pia; Leader, Avi; Pasvolsky, Oren; Iakobishvili, Zaza
Abstract New anti-cancer drugs that inhibit the vascular endothelial growth factor (VEGF) signaling pathway are highly effective in the treatment of solid tumors, however concerns remain regarding their cardiovascular safety. The most common side effect of VEGF signaling pathway (VSP) inhibition is the development of systemic hypertension. We review the incidence, possible mechanisms, significance and management of hypertension in patients treated with VSP inhibitors.